Development of new gastric endoscopic submucosal dissection training model: A reproducibility evaluation study - Mitsui, Tomohiro; Yoda, Yusuke; Sunakawa, Hironori; Takayama, Seiichiro; Nishihara, Keiichiro; Inaba, Atsushi; Sato, Daiki; Minamide, Tatsunori; Takashima, Kenji; Nakajo, Keiichiro; Murano, Tatsuro; Kadota, Tomohiro; Shinmura, Kensuke; Ikematsu, Hiroaki; Yano, Tomonori (Endoscopy International Open, 2022)
Background and study aims Gastric endoscopic submucosal dissection (ESD) is a highly technical procedure mainly due to the distinctive shape of the stomach and diverse locations of lesions. We developed a new gastric ESD training model (G-Master) that could accurately recreate the location of the stomach and assessed the reproducibility of located lesions in the model.Methods The model comprises a simulated mucous membrane sheet made of konjac flour and a setting frame, which can simulate 11 locations of the stomach. We assessed the reproducibility of each location in the model by assessing the procedure speed and using a questionnaire that was distributed among experts. In the questionnaire, each location was scored on a six-point scale for similarity of locations.Results The mean score for all locations was high with > 4 points. Regarding locations, lower anterior and posterior walls had medium scores with 3 to 4 points. The procedure speed was slower in the greater curvature of the upper and middle gastric portions, where ESD is considered more difficult than the overall procedure speed.Conclusions The new gastric ESD training model appears to be highly reproducible for each gastric location and its application for training in assuming actual gastric ESD locations.